Pengaruh Model Pembelajaran Problem Based Learning (PBL) terhadap Kemampuan Pemahaman Konsep Matematis Siswa Kelas XI SMA Swasta Kampus Nommensen Pematangsiantar - Reydy A. Silalahi; Theresia Monika Siahaan; Lois Oinike Tambunan (Journal on Education, 2023)
This study aims to determine whether there is an influence of the Problem Based Learning learning model on students' ability to understand mathematical concepts in Class XI of Private High School Nommensen Pematangsiantar Campus T.A 2022/2023. In this study there is a significant difference between the learning outcomes of students who use the Problem Based Learning learning model and conventional learning models. The population in this study were all students of class XI at the Nommensen Pematangsiantar Private High School, namely 64 people, and the samples in this study were two classes, namely class XI-PMIA as the experimental class and class XI-PIIS as the control class. The research instrument given to the sample is significant, because by using the moment product formula the lowest validity coefficient calculation results are obtained 0.598 (sufficient validity) and the highest validity coefficient is 0.870 (very high validity) so that each test item is valid, using the alpha formula for the test is obtained the results of the calculation of the test reliability coefficient were 0.781 and when compared with rtable with a significant level α = 0.05 and n = 32, it was obtained rtable = 0.361 it turned out that rcount > rtable then the instrument was reliable. This research was conducted on 64 students, the learning outcomes of students who used the Problem Based Learning learning model obtained an average of 64.438, variance of 41.197. The learning outcomes of students using conventional learning models obtained an average of 60.438, a variance of 39.729. From the results of the calculation of the hypothesis test, zcount > ztable is (2.515 > 1.960). Then it is concluded that H0 is rejected and Ha is accepted. This means that the Problem Based Learning learning model influences the ability to understand students' mathematical concepts.